2018
DOI: 10.4236/ajcc.2018.71003
|View full text |Cite
|
Sign up to set email alerts
|

Potential Impacts of Temperature Projections on Selected Large Herbivores in Savanna Ecosystem of Kenya

Abstract: Due to global land surface warming, severe temperature events are expected to occur more frequently and more extremely causing changes in biodiversity and altering movement and survival of large herbivores. There are increasing observations of escalating wildlife range losses worldwide. In this study, we investigated 15 large wild herbivores (4 migratory, 1 dispersing and 10 residents) and their potential range changes in relation to projected temperatures changes based on three Representative Concentration Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 40 publications
(40 reference statements)
0
10
0
Order By: Relevance
“…An exceptionally warm Amboseli ecosystem will lead to decline of most herbivore species as temperature would have surpassed species thresholds temperatures as indicated in the recent studies on potential impacts of climate on wildlife in the savanna ecosystems of Kenya by [45] and [16]. In the study [45] projected that -for RCP 2.6 three out of the 15 species might lose more than 50% of their range by the year 2030s, and 5 out 15 by 2050s and 4 of 15 by 2070s. The second climate scenario of RCP 4.5 projects that by 2030s, 3 species will lose more than 50% of their range, and in 2050s and 2070s 5 species.…”
Section: Discussionmentioning
confidence: 98%
“…An exceptionally warm Amboseli ecosystem will lead to decline of most herbivore species as temperature would have surpassed species thresholds temperatures as indicated in the recent studies on potential impacts of climate on wildlife in the savanna ecosystems of Kenya by [45] and [16]. In the study [45] projected that -for RCP 2.6 three out of the 15 species might lose more than 50% of their range by the year 2030s, and 5 out 15 by 2050s and 4 of 15 by 2070s. The second climate scenario of RCP 4.5 projects that by 2030s, 3 species will lose more than 50% of their range, and in 2050s and 2070s 5 species.…”
Section: Discussionmentioning
confidence: 98%
“…Analysis of historical rainfall data of the study area from 1960-2014 showed a bimodal pattern of rainfall with two rainy seasons and two dry seasons [1]. The year in Amboseli ecosystem begins in October and ends the following September and is linked closely to the annual cycle of growth of vegetation in the study site [46].…”
Section: Discussionmentioning
confidence: 99%
“…A study on potential impacts of projected temperature based on RCP 2.5, 4.5 and 8.5 changes on the elephant range showed minimal impacts on elephant whilst for other large herbivore the impacts on their range will significant [1] It is estimated that there were once more than 350 species of elephants in the world [59] Today we only have two living species of elephant, namely; The African elephant (Loxodonta africana) and the Asiatic elephant (Elephas maximus). Five subspecies are recognized, two belonging to the African elephant and three belonging to the Asiatic elephant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The area experiences a typical East African rainfall pattern, with short rains occurring from November to January and long rains occurring from March to May. Mean annual rainfall is approximately 569 mm, though it has declined since the 1960s (Aduma et al, 2018). Temperatures usually range from 12°C in July to 35°C in February with an average of 21–25°C each month (Worden et al, 2003).…”
Section: Methodsmentioning
confidence: 99%